Objects and Social Actions: On Second-hand Valuation Practices - Frederik Larsen (Copenhagen Business School (CBS), 2015)
In this thesis I address the question of how value is created in second-hand markets. Focusing on the role of charity thrift stores I present an ethnographic account of fieldwork I undertook in the Tavern Guild Community Thrift Store in San Francisco. I analyse my ethnographic findings in light of contemporary literature on values and valuations in material culture and reaching back through the anthropological literature on commodities and gift economies I build a framework around David Graeber's formulation of a concept of social, relational value. In order to structure the analysis I take Mary Douglas's seminal work on classification as a starting point and argue that the practices of valuation constitute a process of transformation form discard to commodity. To support the analysis I introduce theoretical concepts from the ethnographic literature on values, secondhand markets and valuations. Practices of categorization enable the employees to create value, but disorder is a condition of the process, which hinders the flow as well as provides opportunity for value. I describe thrift, a considered use of resources, as the main `infravalue' that drives the valuations and allows the organization to create economic, social and emotional value. Next I zoom in on the interaction between people and objects on a micro-level. The theoretical framework here brings anthropological theory into play with actor-network theory (ANT) approaches to nonhuman actors, and I introduce the term withdrawal from object-oriented philosophy to address the agency of objects in valuations. By dividing the analysis into two parts I demonstrate in greater detail how objects as part of valuations are given agency through social entanglements, but also how the objects by their mere existence influence valuations beyond this entanglement. Their presence as more than the sum of their social relations has a profound impact on the valuations by resisting as much as partaking in the process of transformation. In the last section of the thesis I present an explorative study of the extended trajectory the objects take through markets and wholesale companies in Thailand. I discuss the role of the thrift store in the global context of second-hand exchanges and offer a critical reflection on the consequences of the proliferation of second-hand markets. The thesis provides a situated approach to the study of human-objects interactions and demonstrates that an understanding of the different forms of value that are at play reveal charity thrift organizations as important players in second-hand markets. Thrift enables the organization to salvage as many objects as possible while providing services to the community. In doing so they are vital in transforming discards into commodities for the other actors in the market. This study highlights the importance of considering materiality, and especially objecthood, in the context of second-hand markets, and suggests a situated framework for understanding the relationship between objects and practices in the broader context of material culture studies.
hdl:10398/9182
Keywords: 650